Free to Choose; Returns on Investment in Education in The Netherlands - Odinak, Joop G.; Kunnen, Ruurd (Journal of Income Distribution®, 1999)
In the Netherlands expected (marginal) rates of return for 35 educational paths differ strongly, for both different levels and for different subjects within the same level of education. Private rates of return are somewhat larger than social rates; public sector rates are the smallest. They are low compared to other countries. However, rates based on cross section analyses should be low, if the reference interest rate is corrected for expected wage rises.